EVALUASI KINERJA RUAS JALAN COKROAMINOTO AKIBAT BANGKITAN PERGERAKAN DI LOKASI SEMENTARA PASAR BADUNG - Muh. Rizky Prabowo Tri Subiran; I Wayan Muliawan (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT Denpasar city is growing quite rapidly. The development is quite rapid followed by an increase in movement of people and goods. The development of activities of centers of activity such as markets has increased the rise of travel which tends to lead to conflicts with the movement of traffic flows. The existence of temporary market location Badung cause various traffic problems around the location of the market that is the occurrence of traffic delays due to increased side barriers, traffic congestion which ultimately affects the decreased performance of roads. Data required in this study include primary data and secondary data. The primary data required are traffic volume data, road geometry, speed, side resistance and movement generation. Secondary data obtained from the Central Bureau of Statistics (BPS) Province of Bali is the population of the city of Denpasar. Roadway performance analysis is guided by Indonesian Road Capacity Manual (MKJI). Based on the results of the analysis can be taken that the existence of the temporary location of Badung Market turned out to affect the performance of the road cokroaminoto Denpasar. At peak hour of traffic volume that is at 17.00 - 18.00 has road capacity of 2623.8 smp/hour, degree of saturation of 0.75 and average speed of the vehicle that is equal to 8.15 km/hour. At the peak hour of the movement movement is at 06.15 - 07.15 has a road capacity of 2623.8 smp/hour, the saturation degree of 0.58 and the average speed of the vehicle that is equal to 8.08 km/hour. The level of road service lies at levels D and C. Keyword: volume, capacity, degree of saturation